Li+-conductive Li2SiO3 stabilized Li-rich layered oxide with an in situ formed spinel nano-coating layer: toward enhanced electrochemical performance for lithium-ion batteries. Issue 41 (7th April 2016) - Xu, Mingquan; Lian, Qingwang; Wu, Yuxin; Ma, Cheng; Tan, Pengfei; Xia, Qingbing; Zhang, Jinfang; Ivey, Douglas G.; Wei, Weifeng
Abstract : A novel Li2 SiO3 layered@spinel heterostructured material with superior rate capability and stabilized operating voltage was achieved. Abstract : A novel heterostructured cathode material, comprised of a core of Li-rich layered ( R 3̄ m ) oxides integrated with Li + -conductive Li2 SiO3 and an in situ formed spinel ( Fd 3̄ m ) nano-coating layer, has been successfully synthesized. The ionic conductor Li2 SiO3 in the bulk facilitates the Li + intercalation/deintercalation process and stabilizes the layered structure. This is coupled with the fast 3D Li + diffusion channels of an electrochemically active spinel coating layer, leading to superior rate capability (94 mA h g −1 at 10C) and excellent cycling stability in the heterostructured cathode material. This synergistic strategy may provide some new directions for synthesizing high-performance Li-ion battery cathode materials.